Foreign Direct Investment in Africa-Some Case Studies - Basu, Anupam (IMF Working Papers; Working Paper ;, 2002)
This paper reviews the experiences of a few countries in Sub-Saharan Africa that have succeeded in attracting fairly large amounts of foreign investment. The review indicates that sustained efforts to promote political and macroeconomic stability and implement essential structural reforms have been the key elements contributing to the success that certain countries in Africa have achieved in attracting a substantial volume of FDI. Strong leadership, which has helped promote democracy and overcome social and political strife, and a firm commitment to economic reform have been important determinants. The adoption of sound fiscal and monetary policies, supported by an appropriate exchange rate policy, and a proactive approach to removing structural impediments to private sector activity have had a positive bearing on investor sentiment. The analysis underscores the importance of relying on stability and a broad-based reform effort to encourage foreign investment in Africa.